Manajemen Kurikulum Sekolah Islam Terpadu di SDIT - Mahmud Mahmud; Arismunandar Arismunandar; Andi Nurochmah (EDUSTUDENT: Jurnal Ilmiah Pendidikan dan Pembelajaran, 2022)
This study examined the Management of Integrated Islamic School Curriculum at SDIT Wahdah Islamiyah 01 Makassar. The purpose of research is to know the planning, implementation, and evaluation of the curriculum. This research approach is qualitative. Data analysis techniques use data reduction, data exposure and conclusion withdrawal. Checking the validity of data using trianggulation techniques. The results showed that; (1) In school planning to prepare a curriculum based on the national curriculum combined with wahdah Islamiyah curriculum arranged by the principal, deputy principal of the curriculum section and form a school curriculum team, by trying to show the characteristics of the school (2) In the implementation of curricular, the school teaches general subjects and typical subjects, in learning teachers try to insert religious values in general subjects and carry out the self- development of learners (extracurricular) typical of the school. (3) In the curriculum evaluation, the school evaluates the performance of educators through supervision and the school assesses the learning outcomes of learners through daily evaluation, mid- and final semester evaluations in accordance with the educational calendar. As for the supporting factors, namely, the formation of the school curriculum team and still less effective teachers in implementing the curriculum.Penelitian ini mengkaji tentang Manajemen Kurikulum Sekolah Islam Terpadu di SDIT Wahdah Islamiyah 01 Makassar. Tujuan penelitian untuk mengetahui perencanaan, pelaksanaan, dan evaluasi kurikulum. Pendekatan penelitian ini adalah kualitatif. Teknik analisis data menggunakan reduksi data, paparan data dan penarikan kesimpulan. Pengecekan keabsahan data menggunakan teknik trianggulasi. Hasil penelitian menunjukkan bahwa; (1) Dalam perencanaan sekolah menyusun kurikulum berdasarkan kurikulum nasional yang dipadukan dengan kurikulum khas Wahdah Islamiyah yang di susun oleh kepala sekolah, wakil kepala sekolah bagian kurikulum serta membentuk tim kurikulum sekolah, dengan berusaha memperlihatkan ciri khas sekolah (2) Pada pelaksanaan kurikukulum, sekolah mengajarkan mata pelajaran umum dan mata pelajaran khas, dalam pembelajaran guru berusaha menyisipkan nilai keagamaan pada mata pelajaran umum dan melaksanakan pengembangan diri peserta didik (ekstrakurikuler) khas sekolah. (3) Pada evaluasi kurikulum, sekolah mengevaluasi kinerja tenaga pendidik melalui supervisi dan sekolah menilai hasil belajar peserta didik melalui evaluasi harian, ulangan tengah dan akhir semester sesuai dengan kalender pendidikan. Adapun faktor pendukungnya yaitu, dibentuknya tim kurikulum sekolah dan masih kurang efektifnya guru dalam melaksanakan kurikulum.